Pengaruh teknologi terhadap pendidikan di era globalisasi - Safira, Putri Silviana (Maliki Interdisciplinary Journal, 2024)
Life cannot be separated from development. Specifically in education. People have to keep up with the rapid development of technology. Technology serves as an important component in the education process. Information and communication technology (ICT) can improve the quality of learning. In the era of globalization, technology has become an important part of education to help students and educators in finding references and processing data. The use of this technology facilitates learning methods that prioritize students and allows them to search for various sources of information about learning. The existence of this technology can have both good and bad effects on its users. Positive influences include: 1) being able to complete tasks easily and quickly; 2) being able to communicate with others through email facilities 3) making it easier to find information 4) the education system does not need to be taught face-to-face.